2021
DOI: 10.21134/haaj.v21i1.582
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 Y Su Repercusión en Las Adicciones

Abstract: Objetivo. Indagar acerca de la literatura científica emergente a nivel internacional sobre la repercusión de la pandemia por COVID-19 en las adicciones. Metodología. La base de datos Web of Science se utilizó para analizar la literatura científica sobre la pandemia por COVID-19 y la influencia que ésta pueda tener en el ámbito de las adicciones. Resultados. Se identificaron 320 documentos, de los cuales 38 cumplieron los criterios de inclusión. Sobresalieron tres problemáticas: el consumo de tabaco, opioides y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
2
0
1
Order By: Relevance
“…In March 2020, unprecedented measures were adopted to control the COVID-19 pandemic, including social distancing and mobility restrictions, which meant confining a large part of the population to their homes. In this context, there was an increase in stimuli that produce psychosocial stress [1], as well as modifications in habits and routines in different areas of life, including drug use [2][3][4]. The abuse of legal and illegal drugs became a secondary issue compared to the health risks directly related to COVID-19, even though its impact on health has been well established.…”
Section: Introductionmentioning
confidence: 99%
“…In March 2020, unprecedented measures were adopted to control the COVID-19 pandemic, including social distancing and mobility restrictions, which meant confining a large part of the population to their homes. In this context, there was an increase in stimuli that produce psychosocial stress [1], as well as modifications in habits and routines in different areas of life, including drug use [2][3][4]. The abuse of legal and illegal drugs became a secondary issue compared to the health risks directly related to COVID-19, even though its impact on health has been well established.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, results indicated that male participants reported an increase in the consumption of cigarettes and alcoholic beverages. Some studies show that the stress derived from isolation can be a potential trigger for cigarette and alcohol consumption, which may indicate a maladaptive response to the pandemic ( 46 , 47 ). In contrast, other studies documented that the pandemic encouraged some people to quit smoking, as smoking has been identified as a risk factor for more severe COVID-19 symptoms ( 48 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Se identificó que existe aumento en la probabilidad de presentar un desenlace fatal por COVID-19 en población que fuma tabaco (OR 2,56 -IC 95 % 2,23-2,94; p< 0,05); esto es concordante con lo reportado por Sixto y colaboradores, donde se menciona que existe mayor riesgo de desarrollar la infección por SARS-CoV-2 en fumadores, ya que el virus hace más vulnerables y aumenta la permeabilidad de las células, utilizando como receptor a la enzima convertidora de angiotensina (ACE2). Se relaciona a su vez con la habilidad de los receptores nicotínicos de regular la expresión de la proteína ACE2 en las células del pulmón, lo que puede empeorar el pronóstico (9). Así mismo, se presenta mayor riesgo de un cuadro clínico severo que puede conducir a la muerte en pacientes (10).…”
Section: Discussionunclassified